Enhancing Student Motivation in Virtual Classrooms: the role of vMix technology - Wahyudi, Urip Muhayat Wiji (Indonesian Journal of Curriculum and Educational Technology Studies, 2023)
Motivation plays a crucial role in the success of students' learning activities. The higher the level of individual motivation, the greater the potential for achieving learning outcomes. With the rapid advancement of technology, the field of education is adapting to meet future challenges. As educators, it is essential to innovate and create engaging virtual classrooms that captivate students' interest. Many students show disinterest in attending virtual lectures due to the perceived lack of excitement in these classes. However, there is a technology solution that can address this issue - VMix. VMix offers the capability to create visually appealing and captivating virtual class displays similar to television studios. By integrating VMix with platforms like Zoom and Google Meet, we can enhance the virtual learning experience. This research follows a Research & Development approach and focuses on the development of VMix to enhance student motivation in virtual classrooms. Abstrak Motivasi memiliki peran yang sangat penting dalam keberhasilan kegiatan belajar yang dilakukan oleh mahasiswa. Semakin tinggi motivasi belajar individu maka semakin tinggi prestasi belajarnya untuk dicapai. Perkembangan dunia teknologi yang semakin berkembang memacu dunia pendidikan mulai membentuk dirinya untuk menghadapi masa depan. Pendidikan yang berlangsung di dalam kelas kini bergeser ke dunia maya dan dunia nyata dengan blendended learning. Pendidikan memiliki tujuan untuk menumbuhkan semangat siswa dalam belajar sehingga mampu mengembangkan dirinya. Sebagai pengajar, kita harus berinovasi dalam mengembangkan kelas virtual agar mahasiswa antusias mengikuti perkuliahan. Kebanyakan mahasiswa malas untuk kuliah virtual karena kelas terlihat membosankan . Vmix dapat menghasilkan tampilan kelas virtual yang cantik dan menarik layaknya studio televisi. Hasil tampilan ini bisa kita gabungkan ke zoom, gmeet, Microsoft team, dan lainnya. Metode penelitian yang digunakan dalam penelitian ini adalah Research & Development. Penelitian ini mendeskripsikan pengembangan kelas virtual 3D dalam meningkatkan motivasi belajar mahasiswa di kelas virtual.